Analytical & Experimental Analysis of Lightning Stokes Performance & Protection by MOV Based Simulation Model: A 33 KV Transmission Line Case Study - Arsal Mehmood; Huzaifa Hassan; Faraz Ahmed Baig; Suhail Ahmed Shaikh (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2021)
Researchers are working on techniques to mitigate failure rates as low as possible to avoid potential harm, sustain high power efficiency for this a considerable number of estimation studies were already performed and several designs of methodologies were being suggested. The transmission line performs the role of the arteries which maintain the process of transporting electricity in the transmission line. That is why it is important to maintain and manage the costs of these tracks. Surge arrestor and shield wire application are often techniques chosen for defensive strategy in a very technique. By pushing travelling waves towards the electrical equipment mounted on the transmission line, the effects of lightning stoke on the transmission line may cause severe damage to the electrical equipment. In this review, this research study provides a review-based overview of the mechanism of occurrence of lightning along with its impact on the transmission line and the defence methods used to prevent such effects. A MATLAB / SIMULINK 2020a simulation modeling-based analysis for the incidence of lightning on the 33 kV transmission line system is observed in this regard, and a Metal-Oxide surge arrestor-based lightning fault clearance safety scheme is also suggested and discussed.